Individual, community and health systems factors influencing time to notification of tuberculosis: situating software and hardware bottlenecks in local health systems - Sandra Beauty Chilala; Adam Silumbwe; Joseph Mumba Zulu; Moses Tetui; Maio Bulawayo; Mwimba Chewe; Peter Hangoma (BMC, 2024)
Abstract Background Despite several global interventions, tuberculosis (TB) remains a leading cause of death affecting millions of people globally. Many TB patients either have no access to quality care or go undetected by national health systems. Several multilevel factors account for under-detection of persons with TB. This study sought to explore patient-related software, community and health systems software and hardware factors influencing time to notification of TB in Lusaka District, Zambia. Methods This was an exploratory qualitative case study that adopted a software and hardware lens of conceptualizing health systems. Data were collected from across three sites - urban and peri-urban areas: Chongwe, Kafue, and Lusaka - within Lusaka Province, Zambia. Sixteen key informants - TB corner nurses, community TB treatment supporters, and TB program managers - were interviewed. Six focus groups were held with TB patients. Data were analyzed using thematic analysis. Results The study identified factors influencing timely TB notification, categorized into software and hardware elements. Patient-related software elements, including TB knowledge and awareness, and health-seeking behavior, are crucial for prompt notification among TB patients. In the community health system, software elements like social stigma and undesirable community attitudes towards contact tracing, and hardware elements such as unbalanced schedules, excessive workload and limited capacity of community TB treatment supporters contribute to delayed TB notification. In the formal health system, software elements like negative attitudes of health providers towards TB patients and demotivation of TB staff, and hardware elements such as high diagnostics and transportation costs, outdated diagnostics in primary care facilities, and slow referral mechanisms, can also delay TB notification. Conclusion Delays in time to TB notification are influenced by a combination of software (attitudinal and behavioral) and hardware (resource-related) elements across TB patients, community health systems, community TB treatment supporters, health providers, and TB staff. Addressing these factors, particularly social stigma, negative attitudes, and resource constraints, is crucial to improving timely TB detection and treatment.